An analysis of high-speed isokinetics and pitching - Kluckhuhn, K. L.; Signorile, J. F.; Miller, P. C.; Webber, B. C.; Garcia, M. (Medicine & Science in Sports & Exercise, 1997)
The importance of strength, power, and acceleration were investigated in baseball fastball pitching. The only variables that related to pitching were those associated with speed. Acceleration and power at the fastest movement speeds accounted for almost all fastball pitching variance (99%). Strength was not related to speed of movement and therefore, should not be a variable considered when training for speed. Implication: To improve pitching speed it is necessary to train for speed first. This is best done by consistently trying to move and exceed previous maximum velocity. Any training that does not allow maximum speed in a trial will be useless and could be detrimental.